2019
DOI: 10.18488/journal.aefr.2019.97.778.788
|View full text |Cite
|
Sign up to set email alerts
|

Market Illiquidity Premium on Stock Returns: An Empirical Study of Taiwan Stock Markets

Abstract: This paper examined the existence of illiquidity premiums in Taiwan stock markets during 1982-2016. First, the illiquidity premium was calculated with the method of Amihud (2014) in a whole period and its three sub periods, and then a five-factor model was formed by adding the new risk premium to the traditional Fama-French-Carhart four-factor model. Then quint portfolios the illiquidity measure by Amihud ( 2002) in an ascending order and applies factor models to explore the relationship between stock returns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…India has the highest global mean illiquidity ratio of 3.028, followed by Poland and Romania (Amihud et al, 2019), which motivated us to study premium associated with illiquidity in the Indian stock market. This study has found that the average annual illiquidity premium for the Indian stock market stands at approximately 23%, which is quite high when compared to illiquidity premiums in other markets, such as the US -2.04% to 4% (Amihud & Noh, 2020;Keene & Peterson, 2007), Spain -2.54% (Miralles et al, 2004), Australia -4% (Chan & Faff, 2005), Vietnam -0.11% (Hoang & Phan, 2019), Indonesia -7.68% (Amanda & Husodo, 2015), and Taiwan -16% (Chen et al, 2019). High illiquidity premium in the Indian stock market suggests that stock market illiquidity is of more concern to investors in India than elsewhere.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…India has the highest global mean illiquidity ratio of 3.028, followed by Poland and Romania (Amihud et al, 2019), which motivated us to study premium associated with illiquidity in the Indian stock market. This study has found that the average annual illiquidity premium for the Indian stock market stands at approximately 23%, which is quite high when compared to illiquidity premiums in other markets, such as the US -2.04% to 4% (Amihud & Noh, 2020;Keene & Peterson, 2007), Spain -2.54% (Miralles et al, 2004), Australia -4% (Chan & Faff, 2005), Vietnam -0.11% (Hoang & Phan, 2019), Indonesia -7.68% (Amanda & Husodo, 2015), and Taiwan -16% (Chen et al, 2019). High illiquidity premium in the Indian stock market suggests that stock market illiquidity is of more concern to investors in India than elsewhere.…”
Section: Introductionmentioning
confidence: 84%
“…The main objective of this paper is to price the traded illiquidity factor, which is the differential return premium on illiquid stocks over liquid stocks. The paper constructs and tests the traded illiquidity factor, which is similar to Liu (2006); Amihud et al (2019) and Chen et al (2019). Traded illiquidity tested in the paper is different from the non-traded illiquidity factor, which is a systematic risk of innovations in market illiquidity, tested by Pástor & Stambaugh (2003) and Acharya & Pedersen (2005).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation